Meningkatkan kapasitas anaerob atlet bola basket menggunakan 3x3 small-sided game - Zamzami, Iman Sulaiman; Solahuddin, Soleh; Widiastuti, Widiastuti; Tangkudung, James; Pradityana, Karisdha (Universitas Nusantara PGRI Kediri, 2020)
This research aims to improve the anaerobic capacity and self-esteem of Canton Basketball Club athletes using 3x3 game. This study employs Kemmis and Taggart research model and was conducted in Palembang, Indonesia on March 2018. In this study, fifteen male athletes have volunteered for sixteen training meetings divided into two cycles and have performed 3x3 game with some modifications in each meeting. The Running-based Anaerobic Sprint Test (RAST) and interview are applied to examine the improvement of anaerobic capacity and self-esteem of athletes who perform 3x3 games before and after each cycle. A significant difference of fatigue index is observed. In pretest, the average is 5,35 W/s with a minimum value of 3,83 W/s and maximum value of 6,77 W/s, while in post cycle II is 3,60 W/s with minimum and maximum value of 2,07 W/s and 5,39 W/s respectively. The result of this study reveals that the improvement of anaerobic capacity is various depend on the used modifications. Furthermore, 3x3 game is advantageous to improve anaerobic capacity. Hence, it is suggested that the upcoming studies explore the athletes’ mood and different type of small-sided games as well as its modifications for the improvement of athletes’ performance.